Graphics design work / Shah Izzah Adila Maulad Taib - Maulad Taib, Shah Izzah Adila (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The artwork documents the Sarawak’s indigenous popular harvest foods Terung Dayak, Asam Paya, Tepus, Paku pakis, Paku pakis Uban, and Midin at Pasar Tamu through the understanding of the media dimension. The idea of highlight the texture and shape of the local harvests that are attached as a free-standing stack laden with tetradic pop colors.